2019
DOI: 10.1042/bcj20180522
|View full text |Cite
|
Sign up to set email alerts
|

The KH-type splicing regulatory protein (KSRP) regulates type III interferon expression post-transcriptionally

Abstract: Type III interferons (IFNs) are the latest members of the IFN family. They play an important role in immune defense mechanisms, especially in antiviral responses at mucosal sites. Moreover, they control inflammatory reactions by modulating neutrophil and dendritic cell functions. Therefore, it is important to identify cellular mechanisms involved in the control of type III IFN expression. All IFN family members contain AU-rich elements (AREs) in the 3′-untranslated regions (3′-UTR) of their mRNAs that determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In fact, accumulating evidence suggests that RBPs regulate not only type I IFN, but also type II and type III IFNs. TTP has been shown to mediate IFNγ mRNA decay [56], and KSRP depletion enhances IFNλ3 mRNA stability [57]. These reports further underscore the importance of RBPs in regulating host IFN response.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, accumulating evidence suggests that RBPs regulate not only type I IFN, but also type II and type III IFNs. TTP has been shown to mediate IFNγ mRNA decay [56], and KSRP depletion enhances IFNλ3 mRNA stability [57]. These reports further underscore the importance of RBPs in regulating host IFN response.…”
Section: Discussionmentioning
confidence: 93%
“…Gene set analysis revealed that mRNAs associated with the KH type-splicing regulatory protein (KHSRP) were specifically enriched in endodermal cells (Figure 3G). KHSRP is involved in post-transcriptional regulation of mRNA expression, including IFN λ3 [30]. This could explain the discrepancy between IFN λ2/3 protein and mRNA expression level.…”
Section: Resultsmentioning
confidence: 99%
“…All remaining reported rate constants were assumed to be identical in A549 and Huh7.5 cells). Among the newly introduced parameters, degradation rate constants were fixed based on reported half-lives whenever possible (µCCL5,mRNA, µCXCL10,mRNA, µIFNλ,mRNA, µMX1,mRNA, µIFIT1,mRNA, µMX1, µIFIT1) [93][94][95][96][97][98][99][100]. The degradation of IFN in the supernatant was assumed to be negligible and set to 0.…”
Section: Mathematical Modellingmentioning
confidence: 99%